Digital Nomads and Settler Desires: Racial Fantasies of Silicon Valley Imperialism - McElroy, Erin (Imaginations)

(untitled) (York University, 2019)
This paper investigates the coloniality of contemporary digital nomadism, an identity that numerous Western tech workers use to describe lifestyles of location independence in which they travel the world while maintaining Silicon Valley salaries. Specifically, I assess colonial genealogies of digital nomads and more problematically defined “digital Gypsies.” It was during the height of 19th-century Western European imperialism that Romantic Orientalist texts proliferated, celebrating the racial and sexual “free and wandering Gypsy.” This deracinated figure was used to allegorize colonial desires and imperial violence alike. As I suggest, nomadic racial fantasy undergirds contemporary freedom desires today emergent from the heart of a new empire—that of Silicon Valley. In describing Silicon Valley imperialism and its posthuman digital avatar, I assess how nomadic fantasy transits technologies of gentrification into new frontiers. For instance, sharing economy platforms such as Airbnb celebrate the digital nomad, bolstering contexts of racial dispossession while continuing to deracinate Roma lifeworlds. Might nomad exotica in fact index coloniality and its ability to traverse time and space? How has this fantasy been abstracted over time, also entangling with posthumanist nomadic onto-epistemologies?